The Influence of Beauty Vloggers and Product Quality on Purchase Decision - Nita Kanya; Fahira Adilla (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
The development of make-up in the teenager circle is growing and there are more and more new products that are emerging, where every company has to do more creative marketing and attract new customers so that they can maintain consumer icons in this new image. Make-up is now not only done for personal needs but has become public consumption since the presence of a beauty vlogger. In this era of increasingly sophisticated technology, information about product quality can be obtained by watching content from beauty vloggers This study aims to determine the effect of Beauty Vlogger and Product Quality on the Decision to Purchase Marcks Powder. The method used in this research is the descriptive method and verification method. The results of this study indicate that Beauty Vloggers can be seen to be in a good category, Product Quality can be seen in a good category, and Purchase Decisions can be seen to be in a good category. The T-Test results show that Beauty Vlogger has an effect on Purchase Decisions, and Product Quality has an effect on Purchase Decisions. The F-test shows that Beauty Vlogger and Product Quality affect Purchase Decisions.